2009
DOI: 10.1097/sap.0b013e3181893809
|View full text |Cite
|
Sign up to set email alerts
|

When to Use Drains in Breast Reduction Surgery?

Abstract: We aimed to identify risk factors that may influence surgeons' decision on the use of surgical drains in breast reduction surgery. Medical notes of 182 patients were reviewed. The mean age of the patients was 38 years and the mean body mass index was 25.4 kg/m. Eighty-three percent of the patients had bilateral breast reduction. The mean weight of the breast tissue excised was 581 g, with the inferior pedicle technique being the most commonly used (52.6%). Factors significantly associated with an increased tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Reduction mammaplasties in which NAC repositioning and skin excision are done without drains have been demonstrated to be safe, without increased complications. [30][31][32][33] Additionally, the pain and discomfort associated with wound drainage are avoided, and nursing time involved with drain care is minimized.…”
Section: Discussionmentioning
confidence: 99%
“…Reduction mammaplasties in which NAC repositioning and skin excision are done without drains have been demonstrated to be safe, without increased complications. [30][31][32][33] Additionally, the pain and discomfort associated with wound drainage are avoided, and nursing time involved with drain care is minimized.…”
Section: Discussionmentioning
confidence: 99%
“…Although this arbitrary level has some variation between plastic surgery units, it is common for drains to be removed at ≤30 ml/24 h, and a recent study found that for breast reduction in the UK, only 7.5% did not use this level [2]. This has been the level used in a number of studies assessing the need for drain usage in breast reduction despite the fact that there is no evidence for this practice [7]. Another recent study used ≤20 ml/24 h as the cutoff level for drain removal in breast reduction surgery; again, there was no evidence provided for this rationale [8].…”
Section: Discussionmentioning
confidence: 93%
“…[12][13][14] Similarly, a prospective study conducted by Collis et al 4 on 150 patients was unsuccessful in demonstrating the positive effects of drain usage on hematoma and wound healing, and the authors, referring to Halsted's words from 1893, remarked that "[it is] better not to apply drainage at all than to apply unknowingly. " On the other hand, recommending the utilization of drains in selected breast reduction procedures, Ngan et al 15 have defined these cases as young patients and cases in which less than 500 g is resected. In another study conducted by Borile et al 16 on abdominal dermolipectomy patients, no statistically significant differences were found with respect to hematoma or seroma formation between the two groups in which drains and abdominal corsets were used.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19][20] Numerous publications are available in the literature that compare the efficacy of drainage systems by the types of procedure. 4,[10][11][12][13][14][15][16][17][18][19][20] Moreover, how efficient drains function in the postoperative period, regardless of the surgical procedure type, is another topic that is yet to be studied. No studies are available in the literature about the impact of the type and the size of the drain on its efficacy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation